Desmoglein 1 deficiency results in severe dermatitis, multiple allergies and metabolic wasting. - IRVINE, ALAN (My University, 2013)
The relative contribution of immunological dysregulation and impaired epithelial barrier function to allergic diseases is still a matter of debate. Here we describe a new syndrome featuring severe dermatitis, multiple allergies and metabolic wasting (SAM syndrome) caused by homozygous mutations in DSG1. DSG1 encodes desmoglein 1, a major constituent of desmosomes, which connect the cell surface to the keratin cytoskeleton and play a crucial role in maintaining epidermal integrity and barrier function. SAM syndrome-causing mutations resulted in lack of membrane expression of DSG1, leading to loss of cell-cell adhesion. In addition, DSG1 deficiency was associated with increased expression of a number of genes encoding allergy-related cytokines. The deciphering of the pathogenesis of SAM syndrome substantiates the notion that allergy may result from a primary structural epidermal defect.
PUBLISHED
Keywords: DSG1 deficiency; Immunology, Inflammation & Infection